Can Grit Be Taught? Lessons from a Nationwide Field Experiment with Middle-School Students - Santos, Indhira; Petroska-Beska, Violeta; Carneiro, Pedro; Eskreis-Winkler, Lauren; Munoz Boudet, Ana Maria; Berniell, Ines; Krekel, Christian; Arias, Omar; Duckworth, Angela (World Bank, Washington, DC, 2021)
This paper studies whether a particular socio-emotional skill —grit (the ability to sustain effort and interest toward long-term goals)—can be cultivated and how this affects student learning. The paper implements, as a randomized controlled trial, a nationwide low-cost intervention designed to foster grit and self-regulation among sixth and seventh grade students in primary schools in North Macedonia (about 33,000 students across 350 schools). Students exposed to the intervention report improvements in self-regulation, in particular the perseverance-of-effort facet of grit, relative to students in a control condition. The impacts on students are larger when both students and teachers are exposed to the curriculum than when only students are treated. Among disadvantaged students, the study also finds positive impacts on grade point averages, with gains of up to 28 percent of a standard deviation one year post-treatment. However, the findings also point toward a potential downside: although the intervention made students more perseverant and industrious, there is some evidence that it may have reduced consistency in their interests over time.